Negative infrared photocurrent response in layered WS2/reduced graphene oxide hybrids - Ratha, Satyajit; Simbeck, Adam J.; Late, Dattatray J.; Nayak, Saroj K.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
We report high performance IR photocurrent response of two-dimensional hybrid materials consisting of layered WS2 nanosheets and reduced graphene oxide (RGO). Comparative photocurrent response studies of WS2 nanosheets, RGO, and WS2/RGO hybrids were carried out by performing current-voltage (I-V) and time-dependent current measurements with a laser excitation source having a wavelength of 808 nm. The experimental investigations indicate that WS2/RGO hybrids show negative photocurrent response, whereas WS2 and RGO show positive photocurrent response. The negative photocurrent response of the WS2/RGO hybrids is explained using a band alignment diagram and attributed to a charge transfer mechanism between WS2 and RGO. This analysis is further corroborated by first-principles density functional calculations. The fabricated device based on WS2/RGO hybrids shows a photosensitivity R-lambda of about 6 AW(-1) and a quantum efficiency eta of similar to 924%, which demonstrates high sensitivity of the hybrid material towards IR detection. WS2/RGO hybrids are therefore promising candidates for potential applications in optoelectronic circuits and low cost, high performance, and reliable photodetectors. (C) 2014 AIP Publishing LLC.